Assistance and Capacity Building for Entrepreneurship through Optimization of Field and Sea Products Based on Community Circular Economy - Yuni Ahda; Syahrastani Syahrastani; Anni Faridah; Abdul Razak; Sandi Fransisco Pratama; Siska Alicia Farma; Mariance Dartiani Sagurung; Nadia Sefina; Nagra Aulia Valofi (Fakultas MIPA Universitas Negeri Padang, 2025)
The village of Muara Sikabaluan in the Mentawai Islands faces various challenges in education, economy, and the environment. A community empowerment program based on the circular economy has been implemented to enhance the capacity for processing agricultural and marine products, such as bananas, taro, cassava, and fish. Training in product processing and online and offline marketing was provided to improve the knowledge and skills of residents, especially housewives. The program also promotes the establishment of a village business and economic center as a hub for business development and community welfare improvement. Pretest and posttest results showed significant increases in residents' knowledge and skills related to product processing and the application of circular economy principles. With a participatory and sustainable approach, Muara Sikabaluan Village is expected to become a model for sustainable village development.